Teaching as a human activity : ways to make classrooms joyful and effective - Hatch, J. Amos (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"This is a book for teachers, especially new and soon-to-be teachers. It's a book from one teacher to other teachers who care deeply about what goes on in schools, who see teaching as a calling, who want to make their time in classrooms life changing for the students they are lucky enough to teach. This book is meant to inspire as much as instruct. The lessons that make up the body of this book are organized around five questions that every teacher needs to consider: (1) What can I do to be sure I realize my dream of making a positive difference in the lives of my students? (2) How can I make my teaching effective by building on vital human connections with my students? (3) How can I make my classroom management effective, while encouraging my students to become self-regulating agents of their own behavior? (4) What are instructional approaches that will engage my students in shaping their own development and learning? (5) What can I do to ensure my successful initiation into the teaching profession and avoid burnout in the future? Four lessons are included in each of the five parts defined by these questions. This book celebrates the passion, commitment and intelligence that teachers bring to their profession. Bright, caring individuals are called to teaching because they feel a powerful drive to touch the lives of young people and to make a difference in the world. The approaches advocated in these pages seek to take advantage of the commitment, drive, and brainpower teachers bring to their avocation. The lessons explored foreground the humanity of teaching and highlight ways teachers can experience the satisfaction of sharing meaningful, learning-filled connections with their students"-- Provided by publisher.
Keywords: Effective teaching.; First year teachers.; Teacher effectiveness.; Classroom management.; Teachers -- Job stress -- Prevention.; Education -- Teaching -- General.; Teaching staff.; Teaching skills and techniques.; elektronické knihy; electronic books